2007
DOI: 10.1128/cvi.00215-07
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Poly- N -Acetyl-β-(1,6)-Glucosamine as an Antigen for Diagnosis of Staphylococcal Orthopedic-Prosthesis-Related Infections

Abstract: Staphylococcus aureus and coagulase-negative staphylococci are microorganisms most frequently isolated from orthopedic-implant-associated infections. Their capacity to maintain these infections is thought to be related to their ability to form adherent biofilms. Poly-N-acetyl-␤-(1,6)-glucosamine (PNAG) is an important constituent of the extracellular biofilm matrix of staphylococci. In the present study, we explored the possibility of using PNAG as an antigen for detecting antibodies in the blood sera of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
(38 reference statements)
0
21
0
1
Order By: Relevance
“…High PIA antibody titers have been reported both in patients with SE biofilm prosthesis infections and in healthy controls (26,27). Due to the short incubation time in our experiments, any antibody-dependent complement activation relies on preexisting antibodies.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…High PIA antibody titers have been reported both in patients with SE biofilm prosthesis infections and in healthy controls (26,27). Due to the short incubation time in our experiments, any antibody-dependent complement activation relies on preexisting antibodies.…”
Section: Discussionmentioning
confidence: 89%
“…However, an association between level of anticoagulase-negative staphylococci antibodies and risk of neonatal coagulase-negative staphylococci sepsis has not been documented (32). PIA antibodies mainly belong to the IgG2 subclass (26,33), which are modest complement activators. Our study showed that there are significantly lower antibody titers both toward the biofilm matrix (PIA) and toward the whole bacterium (S. epidermidis SE1457) in cord blood of term infants as compared with adult blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, attempts to design new serology diagnostic assays to diagnose bacterial biofilm infections of orthopedic implants early have failed (7,8). This study shows that high anti-SSPA IgM levels may provide for noninvasive detection of the immune response elicited by biofilm colonization on artificial orthopedic implants, improving patient monitoring with respect to infectious complications.…”
mentioning
confidence: 99%